Algorithms for computational biology : second International Conference, AlCoB 2015, Mexico City, Mexico, August 4-5, 2015 : proceedings /: second International Conference, AlCoB 2015, Mexico City, Mexico, August 4-5, 2015 : proceedings. ([2015]) - Unknown
No abstract available